Situation of residential migration in the labor field in Ecuador, period 2016-2021 - Garzozi-Pincay, René Faruk; Garzozi-Pincay, Yamel Sofía (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Know the current situation of Ecuador with the analysis of migration, its economic and demographic effects. The methods used are exploratory and descriptive research, which allows us to approach the reality facing the country. The result is that in Ecuador it is preferred to hire the migrant for his lower payment, and labor exploitation is incurred towards him. A part of the migrants in Ecuador are professionals, they do not exercise their profession due to the non-legalization of their documents. It is concluded that Ecuador is a chosen destination to obtain resources to send remittances to their country of origin.